Otopolyposis With Middle Ear Allergic Mucin in a Patient With Allergic Fungal Rhinosinusitis. (October 2016) - Kumar, Manvinder S.; Panella, Nicholas J.; Magliocca, Kelly R.; Vivas, Esther X.
Objective: The purpose of this study is to report a case of otopolyposis and middle ear allergic mucin in a patient with allergic fungal rhinosinusitis (AFRS) and no history of middle ear disease and introduce these as possible otologic manifestations of the AFRS. Methods: A case of a 31-year-old female with the aforementioned findings is reported. A review of the pertinent literature was performed. Results: We report a case of a 31-year-old female with a history of AFRS but no history of middle ear disease or hearing loss who presented to our institution complaining of aural fullness. Physical exam was significant for middle ear masses of unknown etiology. Surgical exploration revealed the presence of allergic mucin and middle ear polyposis histologically identical to tissue sampled during prior sinonasal surgeries at the same institution. Aspiration of the middle ear space did not resolve the otologic symptoms. Conclusion: Otopolyposis and middle ear allergic mucin are extremely rare but possible otologic manifestations of AFRS. We encourage otolaryngologists to consider this in the clinical differential diagnosis of patients with a history of AFRS with new onset otologic symptoms.